Schweikian Strategies and Dominants - Fořt, Bohumil (Bohemica Olomucensia, 2023)
In a certain opposition to the commonly accepted view of the good soldier Schweik, the perspective proposed in the study is based on a somewhat heretical assumption (concerning the Švejk-figure), which does not see Schweik as the center of the whole novel as such, but attributes to him a servant function and understands him as the principle of the narrative and semantic construction of this specific text. Therefore, three basic principles, namely physical, verbal, and semantical) of the narrative-semantical build of the text are proposed to help us uncover the novel's general strategies and dominants.
Keywords: Jaroslav Hašek; Good soldier Schweik; narrative strategy; semantic strategy